The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.2105/ajph.76.9.1144
|View full text |Cite
|
Sign up to set email alerts
|

Affirmative action at work: a survey of graduates of the University of California, San Diego, Medical School.

Abstract: PUBLIC HEALTH BRIEFS lamblia as a cause of diarrhea in children, especially among a day care population. A recent study indicates that thorough handwashing in day care centers may help prevent its dissemination.24 Early recognition and treatment may be necessary to prevent its spread in the community. ACKNOWLEDGMENTSWe are indebted to Donald G. Thomas for making available to us the computer program25 for carrying out the computations for Tables I and 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…It is also consistent with two studies of doctors in California (Penn et al 1986;Davidson and Lewis 1997) that found weaker credentials on paper but little difference in observable performance between minorities/women admitted to medical school under Affirmative Action and their white male counterparts.47…”
Section: Discussionsupporting
confidence: 87%
“…It is also consistent with two studies of doctors in California (Penn et al 1986;Davidson and Lewis 1997) that found weaker credentials on paper but little difference in observable performance between minorities/women admitted to medical school under Affirmative Action and their white male counterparts.47…”
Section: Discussionsupporting
confidence: 87%
“…This interpretation is consistent with anecdotal evidence provided by Caplan (1997), who argues that Affirmative Action requirements are flexible enough that employers can adapt to them in ways that are not very costly (and are sometimes beneficial) over the longer term. It is also consistent with two studies of doctors in California (Penn et al, 1986;Davidson and Lewis, 1997) that found weaker credentials on paper but little difference in observable performance between minorities/females admitted to medical school under Affirmative Action and their white male counterparts. 43 56 44 For evidence on administrative and enforcement costs of EEO and Affirmative Action, see Conrad (1995).…”
supporting
confidence: 90%
“…The results show quite uniformly that "special admit" and even more so minority physicians are more likely to treat patients who are minorities, poor (especially those paying through Medicaid), non-English speakers, and/or those located in rural/inner-city (or "physician shortage") areas (Keith, et al, 1987;Penn, et al, 1986;and Cantor, et al, 1996;Komaromy, et al, 1996). Thus, the special admissions programs seem to be generating social benefits to disadvantaged groups that go beyond the physician in question.…”
Section: Gains Experienced By Beneficiaries Of Preferential Admissionmentioning
confidence: 99%